A Broad Spectrum Chemokine Inhibitor Prevents Preterm Labor but Not Microbial Invasion of the Amniotic Cavity or Neonatal Morbidity in a Non-human Primate Model - Coleman, Michelle; Orvis, Austyn; Wu, Tsung-Yen; Dacanay, Matthew; Merillat, Sean; Ogle, Jason; Baldessari, Audrey; Kretzer, Nicole M.; Munson, Jeff; Boros-Rausch, Adam J.; Shynlova, Oksana; Lye, Stephen; et al. (Frontiers in Immunology, 2020)
Leukocyte activation within the chorioamniotic membranes is strongly associated with inflammation and preterm labor (PTL). We hypothesized that prophylaxis with a broad-spectrum chemokine inhibitor (BSCI) would downregulate the inflammatory microenvironment induced by Group B Streptococcus (GBS, Streptococcus agalactiae) to suppress PTL and microbial invasion of the amniotic cavity (MIAC). . To correlate BSCI administration with PTL and MIAC, we used a unique chronically catheterized nonhuman primate model of Group B Streptococcus (GBS)-induced PTL. In the early third trimester (128-138 days gestation; ~29-32 weeks human pregnancy), animals received choriodecidual inoculations of either: (1) saline (N=6), (2) GBS, 1-5x108 colony forming units (CFU)/ml; N=5), or (3) pre-treatment and daily infusions of a BSCI (10 mg/kg intravenous and intra-amniotic) with GBS (1-5x108 CFU/ml; N=4). We measured amniotic cavity pressure (uterine contraction strength) and sampled amniotic fluid (AF) and maternal blood serially and cord blood at delivery. Cesarean section was performed 3 days post-inoculation or earlier for PTL. Data analysis used Fisher’s exact test, Wilcoxon rank sum and one-way ANOVA with Bonferroni correction. Saline inoculation did not induce PTL or infectious sequelae. In contrast, GBS inoculation typically induced PTL (4/5, 80%), MIAC and fetal bacteremia (3/5; 60%). Remarkably, PTL did not occur in the BSCI+GBS group (0/4, 0%; p=0.02 vs. GBS), despite MIAC and fetal bacteremia in all cases (4/4; 100%). Compared to the GBS group, BSCI prophylaxis was associated with significantly lower cytokine levels including lower IL-8 in amniotic fluid (p=0.03), TNF- in fetal plasma (p<0.05), IFN- and IL-7 in the fetal lung (p=0.02) and IL-18, IL-2, and IL-7 in the fetal brain (p=0.03). Neutrophilic chorioamnionitis was common in the BSCI and GBS groups, but was more severe in the BSCI+GBS group with greater myeloperoxidase staining (granulocyte marker) in the amnion and chorion (p<0.05 vs. GBS). Collectively, these observations indicate that blocking the chemokine response to infection powerfully suppressed uterine contractility, PTL and the cytokine response, but did not prevent MIAC and fetal pneumonia. Development of PTL immunotherapies should occur in tandem with evaluation for AF microbes and consideration for antibiotic therapy.